Optimal investment under cost uncertainty - Jerome Detemple; Yerkin Kitapbayev (Risks, 2018)
This paper studies the valuation of real options when the cost of investment jumps at a random time. Three valuation formulas are derived. The first expresses the value of the project in terms of a collection of knockout barrier claims. The second identifies the premium relative to a project with delayed investment right and prices its components. The last one identifies the premium/discount relative to a project with constant cost equal to the post-jump cost and prices its components. All formulas are in closed form. The behavior of optimal investment boundaries and valuation components are examined.
Keywords: 330; American option; real options; optimal stopping; random strike; early exercise premium; free-boundary problem